PHILOSOPHICAL APPROACH TO THE ANALYSIS OF MODERN PEDAGOGICS (IN THE ANNEX TO UKRAINE) - Джура, Сергей Георгиевич (Eastern-European Journal of Enterprise Technologies, 2012)
In article the science purposes as a whole and pedagogics as sciences in particular are considered. The problem of criterion function of pedagogics and prospect of its decision is shown. Main, in opinion, authors the purpose, isn't demanded yet in Ukraine.